Design, Synthesis and Application of Fluorine-Labeled Taxoids as (19)F NMR Probes for the Metabolic Stability Assessment of Tumor-Targeted Drug Delivery Systems - Seitz, Joshua D. (J Fluor Chem, 2014)
Novel tumor-targeting drug conjugates, BLT-F(2) (1) and BLT-S-F(6) (2), bearing a fluorotaxoid as the warhead, a mechanism-based self-immolative disulfide linker, and biotin as the tumor-targeting module, were designed and synthesized as (19)F NMR probes. Fluorine atoms and CF(3) groups were strategically incorporated into the conjugates to investigate the mechanism of linker cleavage and factors that influence their plasma and metabolic stability by real-time monitoring with (19)F NMR. Time-resolved (19)F NMR study on probe 1 disclosed a stepwise mechanism for release of a fluorotaxoid, which might not have been detected by other analytical methods. Probe 2 was designed to bear two CF(3) groups in the taxoid moiety as “3-FAB” reporters for enhanced sensitivity and a polyethylene glycol oligomer insert to improve solubility. The clean analysis of the linker stability and reactivity of drug conjugates in blood plasma or cell culture media by HPLC and (1)H NMR is troublesome, due to the overlap of key signals/peaks with background arising from highly complex ingredients in biological systems. Accordingly, the use of (19)F NMR would provide a practical solution to this problem. In fact, our “3-FAB” probe 2 was proven to be highly useful to investigate the stability and reactivity of the self-immolative disulfide linker system in human blood plasma by (19)F NMR. It has also been revealed that the use of polysorbate 80 as excipient for the formulation of probe 2 dramatically increases the stability of the disulfide linker system. This finding further indicates that the tumor-targeting drug conjugates with polysorbate 80/EtOH/saline formulation for in vivo studies would have high stability in blood plasma, while the drug release in cancer cells proceeds smoothly.